Efektivitas Evaluasi Pembelajaran dalam Meningkatkan Prestasi Belajar Siswa di SD N Larangan Tokol 1 Pamekasan - Gita Puspita Sari; Nili Fauziah; Emna Laisa; Fitria Fitria (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2026)
This study aims to explain the effectiveness of assessment in the learning process, focusing on improving student outcomes at SDN Larangan Tokol 1 Pamekasan. This research applies a qualitative methodology categorized as a descriptive study. Data collection was carried out through observation, interview sessions, and document analysis involving teachers and students at SDN Larangan Tokol 1 Pamekasan The findings of the study indicate that the implementation of learning process evaluation is conducted systematically and continuously through question and answer activities, daily assignments, group discussions, learning practice, daily tests, as well as the assessment of students’ attitudes and skills. Teachers use various strategies to improve the effectiveness of learning evaluation, such as the use of varied teaching methods, providing motivation, habituation of discipline, utilization of learning media, and the implementation of remedial and enrichment programs.Supporting factors for the effectiveness of learning evaluation include the support of the principal, teacher competence, parental support, and the availability of learning facilities. Meanwhile, the obstacles include differences in students’ learning abilities, lack of motivation among some students, and limited availability of certain learning media.The assessment of the learning process contributes effectively to improving students’ academic achievement, shaping discipline and responsibility character, as well as increasing students’ participation and collaboration in the ongoing learning process. Therefore, learning assessment plays a crucial role in creating an effective learning process and improving student achievement at SDN Larangan Tokol 1 Pamekasan.